Pelatihan dan Pengembangan Kompetensi bagi RedSeller melalui Promosi Digital Multiplatform - Bela Lusiana Defi; Rizky Dermawan (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid development of digital technology has significantly transformed marketing strategies, particularly in the accommodation service sector, which relies heavily on digital visibility and consumer trust. Social media has become a strategic promotional tool due to its ability to reach consumers widely, quickly, and interactively. However, many reseller-based digital marketers, including RedSeller participants, still face limitations in digital competencies, especially in managing social media in a planned and integrated manner. This community service activity aims to enhance the digital competencies of RedSeller participants through a social media workshop focused on multiplatform digital promotion. The methods employed include interactive lectures, discussions, demonstrations, and hands-on practice in managing promotional content on Instagram, Facebook, TikTok, and X. The results indicate improvements in participants’ understanding of digital marketing concepts, content creation strategies, and the utilization of social media features to increase promotional reach and engagement. Furthermore, participants demonstrated enhanced skills in developing more engaging, consistent, and target-oriented promotional content. This activity plays an important role in strengthening participants’ digital marketing competencies and supporting the sustainability of social media-based promotional strategies in the accommodation service sector.